Effect of Small Percentages of Certain Metals upon the Compressibility of Lead at an Elevated Temperature - Lyall Zickrick (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
NUMEROUS brands of virgin pig lead are used in the manufacture of lead and lead-alloy cable sheath for commercial cables. In changing from one brand of pig lead to another a readjustment of press operating conditions is nearly always necessary. This is due largely to different flow characteristics, and some brands extrude at a much lower pressure than others; for example, copper-bearing lead requires much more pressure than a low-bismuth lead under the same operating conditions. With the modern type of lead press the extrusion practice in general differs very little. Molten lead at a temperature of 375° to 400° C. (710° to 750° F.) is cast in a water-cooled cylinder and allowed to cool or solidify into a slug for six to nine minutes. . This slug is forced into the die block and around the core tube through which the cable runs. The die block is held at an optimum temperature by means of gas flames, usually 175° to 225° C. (350° to 4.35° F.). Measurements of the tem¬perature of the cable sheath taken at the time of extrusion have covered a range of 190° to 225° C. (375° to 435° F.). According to Tammann, the rate of extrusion for a metal under constant pressure through a simple orifice is almost doubled for each 10° C. rise in temperature. Because of the irregularity of die-block construction, such a great increase is not obtained in lead-cable extrusion practice. To obtain more" definite information about the effect of small per¬centages of metals usually present as impurities in virgin pig lead, a series of compression tests were made covering several different brands of lead and various alloys. Since the usual temperature of the sheath is approxi¬mately 200.° C. as it emerges from the die block, these compression tests were all performed at 200° C. Five different brands of virgin pig lead were selected, as follows: Brand A: A desilverized western lead of very high purity. This lead contains neither copper nor bismuth. Brand B: A bismuth-free southeastern Missouri lead, usually con¬taining 0.05 to 0.08 per cent copper. Brand C: A copper-free mid-western desilverized lead of very good grade, usually containing around 0.06 to 0.10 per cent bismuth.